An Examination of Father Vulnerability and Coercive Family Process after the Birth of a Sibling: A Spillover Cascade Model - Stevenson, Matthew M. (Dev Psychopathol, 2018)
Fathers are a crucial source of support for children following the birth of an infant sibling. This study examined whether fathers were more vulnerable to the effects of interparental conflict than mothers, and whether there was a subsequent spillover cascade from interparental conflict to children’s externalizing behavior problems. We followed 241 families after the birth of a second child. Mothers and fathers reported on interparental conflict and parental efficacy at 1 and 4 months postpartum and punitive discipline and firstborn children’s externalizing behavior problems across a longitudinal investigation (prenatal, 4, 8 and 12 months postpartum). For both mothers and fathers, interparental conflict prenatally predicted decreased parental efficacy following the birth. Fathers’ lower parental efficacy was significantly associated with increased punitive discipline toward the older sibling at 4 months, whereas mothers’ lower parental efficacy was not. Coercive family processes were present between mothers’ and fathers’ punitive discipline and older siblings’ externalizing behavior problems. Results were inconsistent with the father vulnerability hypothesis in that both mothers and fathers were both vulnerable to interparental conflict, which in turn, spilled over to create coercive family processes that exacerbated children’s externalizing behavior problems in the year following the birth of a second child.